2015
DOI: 10.1139/cjfas-2014-0433
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation structure of a semi-anadromous fish in a dynamic environment

Abstract: The Sacramento splittail (Pogonichthys macrolepidotus) is a relatively large (400 mm), long-lived (8 years) demersal cyprinid of conservation importance endemic to the San Francisco Estuary (SFE), California, USA. It exhibits a semi-anadromous life cycle spending adult life in low to moderate salinity (0-12) habitat with migrations into upstream freshwater rivers and floodplains for spawning during winter-spring. The species persists as two genetically distinguishable populations -one dominant and one subordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…We restricted our Striped Bass analysis to age-0 fish to minimize the potential effects of ontogenetic changes in habitat use and distribution and because older age classes are likely much less vulnerable to these sampling methods. In contrast with the other focal species, Sacramento Splittail is a littoral species (Feyrer et al 2005(Feyrer et al , 2015 and likely not as vulnerable as the pelagic species to the sampling methods used in the three surveys.…”
Section: Datamentioning
confidence: 91%
“…We restricted our Striped Bass analysis to age-0 fish to minimize the potential effects of ontogenetic changes in habitat use and distribution and because older age classes are likely much less vulnerable to these sampling methods. In contrast with the other focal species, Sacramento Splittail is a littoral species (Feyrer et al 2005(Feyrer et al , 2015 and likely not as vulnerable as the pelagic species to the sampling methods used in the three surveys.…”
Section: Datamentioning
confidence: 91%
“…2 ). Also taken into consideration were environmental salinity measurements at seine and trawl locations when capturing the wild fish used in the experiments reported here and published observations during wild capture suggesting that splittail are not found at salinities >16‰ in the wild ( Feyrer et al ., 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…If the ocean spatial associations found in this study are also found in other migratory species that exhibit philopatry to feeding or breeding grounds, then maintaining an association with individuals from the same genetic or natal origin during migration may represent an underappreciated process that aids in the successful return of individuals to habitats that confer fitness benefits (Feyrer et al 2015). The ability to recognize and associate preferentially with individuals from the same genetic or natal group is common across animal taxa (mammals, Porter et al 2001;birds, Senar et al 1990;reptiles, Bull et al 2000;insects, Clark et al 1995) and is particularly prevalent in fishes (Griffiths 2003).…”
Section: Discussionmentioning
confidence: 70%
“…To the extent that membership in such aggregations is stable, understanding the number, size and distributions of aggregations, could help predict the influence of stock-specific fishing mortality. The rich literature on models of predator encounter with fish prey schools may play a more pivotal role in improving fisheries management and conservation than previously recognized (Czaran 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation